2006
DOI: 10.1677/erc.1.01123
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of ERα at serine 118 in primary breast cancer and in tamoxifen-resistant tumours is indicative of a complex role for ERα phosphorylation in breast cancer progression

Abstract: Oestrogen receptor-a (ERa) is an important prognostic marker in breast cancer and endocrine therapies are designed to inhibit or prevent ERa activity. In vitro studies have indicated that phosphorylation of ERa, in particular on serine 118 (S118), can result in activation in a ligandindependent manner, thereby potentially contributing to resistance to endocrine agents, such as tamoxifen and aromatase inhibitors. Here we report the immunohistochemistry (IHC) of S118 phosphorylation in 301 primary breast tumour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
83
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 50 publications
6
83
1
Order By: Relevance
“…In this context, elevated HER2 and EGFR expression have been observed in cell line models of tamoxifen resistance, whilst elevated ERK1/2 MAPK [7] and high levels of phosphorylated AKT have been associated with poor response to tamoxifen and a worse patient prognosis [8]. Further, phosphorylation of ERα at serine 118 (S118) is elevated in recurrence following tamoxifen treatment [9]. Finally, high-level expression of the coactivator AIB1 is associated with poor response to tamoxifen in ERα-positive breast cancer, with AIB1-and HER2-positive patients having the worst outcome following tamoxifen treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, elevated HER2 and EGFR expression have been observed in cell line models of tamoxifen resistance, whilst elevated ERK1/2 MAPK [7] and high levels of phosphorylated AKT have been associated with poor response to tamoxifen and a worse patient prognosis [8]. Further, phosphorylation of ERα at serine 118 (S118) is elevated in recurrence following tamoxifen treatment [9]. Finally, high-level expression of the coactivator AIB1 is associated with poor response to tamoxifen in ERα-positive breast cancer, with AIB1-and HER2-positive patients having the worst outcome following tamoxifen treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…Roughly, 70% of human breast tumors express significant levels of estrogen receptor alpha (ERα) (1), making antiestrogen therapy an important therapeutic modality in breast cancer treatment (2)(3)(4) There is extensive data supporting various correlations between ERα phosphorylation patterns and sensitivity to antiestrogen therapy and clinical indicators of treatment response (delayed disease progression/ improved survival) (6)(7)(8)(9)(10). ERα phosphorylation of serine residues in the activation domain function 1 (AF-1) leads to enhanced ERα-driven transcription via modulation of coactivators recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…Sarwar et al (2006) demonstrated that pERa-Ser118 was elevated in tumor biopsies taken from patients who had relapsed following TAM treatment. Yamashita et al (2008) revealed that a higher expression of pERa-Ser118 was a predictor of poorer survival.…”
Section: Discussionmentioning
confidence: 98%
“…EGFR, HER2, and IGF1R) (Gee et al 2005, Nicholson et al 2007, Moerkens et al 2014). In addition, increased activation of their downstream targets ERK and PI3K/Akt leading to increased pERa-Ser118 and/or pERa-Ser167 have been observed (Gee et al 2001, Yamashita et al 2005, Sarwar et al 2006. It has been widely reported that IL6 plays a critical role in the development and progression of OVCA (Syed et al 2002, Nilsson et al 2005, Rabinovich et al 2007, Yang et al 2009, Wang et al 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation